Comparison of nanoparticle-selenium, selenium-enriched yeast and sodium selenite on the alleviation of cadmium-induced inflammation via NF-kB/IκB pathway in heart - Ge, Jing; Guo, Kai; Zhang, Cong; Talukder, Milton; Lv, Mei-Wei; Li, Jin-Yang; Li, Jin-Long (The Science of the total environment, 2021)
Cadmium (Cd) has been confirmed as an environmental contaminant, which potential threats health impacts to humans and animals. Selenium (Se) as a beneficial element that alleviates the negative effects of Cd toxicity. Se mainly exists in two forms in food nutrients including organic Se usually as (Se-enriched yeast (SeY)) and inorganic Se (sodium selenite (SSe)). Nanoparticle of Se (Nano-Se), a new form Se, which is synthesized by the bioreduction of Se species, which attracted significant attention recently. However, compared the superiority alleviation effects of Nano-Se, SeY or SSe on Cd-induced toxicity and related mechanisms are still poorly understood. The purpose of this study was to compare the superiority antagonism effects of Nano-Se, SeY and SSe on Cd-induced inflammation response via NF-kB/IκB pathway in the heart. The present study demonstrated that exposed to Cd obviously increased the accumulation of Cd, disruption of ion homeostasis and depressed the ratios of K+/Na+ and Mg2+/Ca2+ via ion chromatography mass spectrometry (ICP-MS) detecting the heart specimens. In the results of histological and ultrastructure observation, typical inflammatory infiltrate characteristics and mitochondria and nuclear structure alterations in the hearts of Cd group were confirmed. Cd treatment enhanced the inducible nitric oxide synthase (iNOS) activities and NOS isoforms expression via NF-kB/IκB pathway to promote inflammation response. However, the combined treatment of Cd-exposed animals with Nano-Se was more effective than SeY and SSe in reversing Cd-induced histopathological changes and iNOS activities increased, reducing Cd accumulation and antagonizing Cd-triggered inflammation response via NF-kB/IκB pathway in chicken hearts. Overall, Se applications, especially Nano-Se, can be most efficiently used for relieving cardiotoxicity by exposed to Cd compared to other Se compound. The present study performs a novel insight on the protective comparative of different Se sources (Nano-Se, SeY, SSe) to Cd-induced cardiotoxicity via NF-kB/IκB pathway. [Display omitted] •Nano-Se obviously mitigated Cd-induced cardiac injury.•Nano-Se relieved disruption of element balance and Cd accumulation.•Nano-Se attenuated Cd-induced inflammation response via NF-kB/IκB signaling pathway.•Nano-Se was superior to SeY and SSe in alleviating Cd caused cardiotoxicity.